Respiratory failure and central nervous system injury caused by mixed gas poisoning after inhaling naphtha vapor: three case reports - Shan, Zhaozhao; Liu, Jianjian; Shang, Ruikai; Liu, Hongyu; Tian, Qiaoxin; Liu, Yuru; Zheng, Yingying; Jian, Xiangdong; Kan, Baotian (Frontiers in Medicine, 2025)
ObjectiveIn March 2025, a rare incident of acute group poisoning due to naphtha vapor inhalation occurred in Shandong, China. This study aimed to analyze the clinical data of patients exposed to mixed asphyxiating gases to enhance awareness of relevant personnel in industrial production and emergency medical staff.MethodsAn on-site investigation and laboratory testing were conducted to examine the poisoning incident. The clinical data of three patients poisoned by asphyxiating gases after inhaling naphtha vapor were retrospectively analyzed.ResultsPatients were primarily exposed to naphtha vapor through the respiratory tract. The main clinical manifestations were respiratory failure and neurological symptoms, such as impaired consciousness. Chest computed tomography and cranial magnetic resonance imaging revealed varying degrees of injury in all three patients, primarily characterized by hypoxic–ischemic brain lesions, pulmonary inflammation, and exudation. Laboratory tests showed arterial blood gas hypoxemia, abnormal white blood cell count, and an increased neutrophil ratio. After mechanical ventilation, glucocorticoid pulse therapy, and neurotrophic treatment, one patient recovered fully within 7 days, one exhibited persistent decorticate symptoms, and one continued to experience respiratory failure requiring mechanical ventilation. All three patients survived.ConclusionInhalation of naphtha vapor led to varying degrees of respiratory failure and neurological impairment in all three patients. Based on on - site sampling analysis and laboratory tests, it was determined that this incident was a poisoning incident caused by inhalation of a mixed gas mainly composed of hydrogen sulfide and alkane gases due to non - compliant operations. Early electrocardiogram monitoring combined with imaging evaluation played a crucial role in guiding clinical management and improving outcomes.